Tradiční rodina v Číně - Dosedlová, Aneta (Masaryk University Press, 2019)
Title in English: Traditional family in China This book focuses on togetherness within a Chinese traditional family. Step by step, the specific structure of this kind of family, and the set of social codes and regulations it uses, unfolds. Although what is being discussed is an ideal image of a family, it has to be taken into account as the model which real families follow. In eight chapters, specific cultural and social phenomena are described, being, in the realm of the living: family, matrimony, and child-rearing; in the realm of the dead: ancestor worship, funeral rites, and visions of afterlife; and finally on the spiritual level, folk religion, traditional festivities, and attempts to change one's destiny. For better understanding, the text is supplemented with pictures.